Analysis of Factors Influencing Ankle-Brachial Index Values in Patients with Diabetes Mellitus - Achmad Syukkur; Emy Sutiyarsih (GLOBAL HEALTH SCIENCE GROUP, 2026)
Peripheral artery disease (PAD) is one of the chronic complications that frequently occurs in patients with diabetes mellitus (DM). PAD can be detected early using the non-invasive Ankle-Brachial Index (ABI) method. An abnormal ABI value may indicate impaired peripheral blood flow and serves as an important indicator of the risk of amputation and cardiovascular morbidity. The aim of this study was to analyze the factors affecting ABI values in patients with DM, namely age, sex, Body Mass Index (BMI), duration of DM, smoking status, physical activity, foot care status, history of DM complications, adherence to DM therapy, and blood glucose levels. This research employed a quantitative descriptive non-experimental approach with a cross-sectional design. The sample was obtained through accidental sampling, resulting in 106 respondents. Data were analyzed using the Spearman’s rho correlation test. The findings revealed that factors significantly associated with ABI values included duration of DM (p = 0.000), smoking status (p = 0.029), foot care status (p = 0.000), history of DM complications (p = 0.000), adherence to DM therapy (p = 0.000), and blood glucose levels (p = 0.000). The results of this study are expected to encourage respondents, particularly DM patients, to improve their overall adherence to diabetes therapy.